The role of extracellular signal-regulated kinase in beta-adrenoceptor-mediated vasodilatation - Uhiara, Chukwuemeka Obinna (2012)
Beta-Adrenoceptors (B-ARs) mediate vasodilatation by activating various mechanisms that collectively contribute to vascular smooth muscle (VSM) relaxation. It has been shown that B2-AR stimulation in cultured cells results in activation of extracellular signal-regulated kinase (ERK). As the functional relevance of this was not known, the aim of the current investigation was determine the role of ERK in beta-AR-mediated vasodilatation. Isoprenaline-induced relaxation of porcine coronary artery (PCA) segments pre-contracted with the thromboxane mimetic U46619 was significantly enhanced by inhibition of ERK activation. Relaxations to the beta2-AR agonist salbutamol, but not those to the beta1-AR agonist xamoterol or the adenylyl cyclase activator forskolin, were also enhanced. The intermediate-conductance Ca2+-activated K+ (IKCa) channel blocker TRAM-34 prevented the enhancement of beta2-AR-mediated responses. Taken together, the data indicate that ERK inhibits beta2-AR-mediated vasodilatation by interacting with a cyclic 3’, 5’-adenosine monophosphate-independent relaxation pathway involving K+ channels. This may occur through a direct regulatory action on the IKCa channel via phosphorylation. Furthermore, the finding that increased ERK activation in a rat model of Type II diabetes was associated with significantly impaired beta-AR-mediated vasodilatation raises the possibility that ERK may represent a promising therapeutic target in the treatment of disease states characterised by abnormal vascular function.